Tumor volume and tumor sphericity as prognostic factors in patients with primary oral cancer. (October 2021) - Lucchi, E.
Abstract : Purpose: We analyzed the prognostic impact of 3D tumor characteristics, tumor volume and tumor sphericity, on the survival of patients with primary oral cancer. Methods: We identified 73 patients from our database that underwent a surgical treatment from 2006 to 2021. The pre-operatory CT were uploaded in an appropriate software to segment the tumor mass with threshold tools. Afterwards we obtained the corresponding volume and sphericity (numeric index of the regularity of the tumor surface). The average follow-up was 22 months. Results: In the subgroup of tongue mean tumor volume was significantly lower in patients without recurrence of disease (4.48 vs 18.10cm3 with p=0.009), whereas mean tumor sphericity was significantly different in the subgroup of adherent gingiva in relation to recurrence or death tumor-related (respectively 0.62 vs 0.51 with p=0.025; 0.63 vs 0.54 with p=0.006). Survival was significantly greater for patients with a tumor volume inferior to cut-off value (recurrence-free survival 78.0% vs 28.6% with p<0.01; overall survival 88.3% vs 46.2% with p=0.001). We obtained a similar result for the subgroup of tongue (recurrence-free survival 78.9% vs 0.0% with p=0.028; overall survival 92.3% vs 41.7% with p=0, 022), whereas for the subgroup of adherent gingiva survival was worse in patients with a sphericity index inferior to cut-off (recurrence-free survival 88.2% vs 30.0 with p<0.01; overall survival 96.6% vs 73.3% with p=0, 014). Conclusions: Three-dimensional parameters, tumor volume and tumor sphericity, characterize better the size and shape of each case, adding information that could be useful to delineate the prognosis for oral cancer.